Ginsenoside Rh4 remodels the periphery microenvironment by targeting the brain-gut axis to alleviate depression-like behaviors. (15th March 2023) - Shao, Jingjing; Ma, Xiaoxuan; Qu, Linlin; Ma, Pei; Huang, Rong; Fan, Daidi
Graphic abstract: Highlights: For the first time found ginsenoside Rh4 can alleviate depression behavior in mice. Rh4 alleviates neuroinflammation by inhibiting NLRP3/caspase-1/IL-1β signaling. Rh4 attenuates CUMS-induced hippocampal nerve damage in mice. Rh4 ameliorates CUMS-induced gut dysbiosis and barrier impairment. Rh4 alleviates depression-like behaviors by targeting the brain-gut axis in mice. Abstract: Depression is a neuropsychiatric disease that threatens the physical and mental health of humans worldwide. This study explored the potential anti-depressant effects of ginsenoside Rh4 and its mechanisms of action. The results showed that Rh4 could significantly inhibit depression-like behavior in the depression mouse model and alleviate neuronal damage and hypothalamic–pituitary–adrenal axis disorder. Concurrently, Rh4 inhibits hippocampal neuronal apoptosis and synaptic structural damage due to the overexpression of proinflammatory cytokines and overactivation of microglia and astrocytes by inhibiting the immune-inflammatory response and signaling molecular interaction pathways. Rh4 can also improve intestinal flora and increase the short-chain fatty-acids content. The correlation analysis indicated that the Rh4-inhibited LPS/NLRP3/caspase-1/IL-1β signaling pathway plays a key role in ameliorating depression. Therefore, this study provides valuable insights into the mode of action of Rh4 on the brain-gut axis in depression, suggesting that Rh4 may be a promising clinical drug for the treatment of depression.